RETRACTED (ditarik) : Science Literacy in Early Childhood: Development of Learning Programs in the Classroom - Choiriyah; Lutfiani, Ninda; Khoirunisa, Alfiah; Faturahman, Adam; Nabila, Efa Ayu (Aptisi Transactions On Technopreneurship (ATT), 2021)
Following rigorous, careful concerns and communication between the publisher and the authors of the article published in Aptisi Transactions on Technopreneurship to article entitled “Science Literacy in Early Childhood: Development of Learning Programs in the Classroom” Vol 3, No 2, pp. 30-36, September 2021. This paper has been withdrawn at the request of the author and has been retracted. The article contained redundant material, the author has informed the editor that the paper was published in the Indonesian Journal of Early Childhood Education Studies, 10(2), pp. 136-142. The publisher apologizes to the authors and readers for the error and any inconvenience caused.